Processing-structure-property relationships in practical thin solid-electrolyte separators for all-solid-state batteries - Junhao Li; Soochan Kim; Lorenzo Mezzomo; Yvonne Chart; Jack Aspinall; Riccardo Ruffo; Mauro Pasta (JPhys Energy, 2024)
Scalable processing of thin and robust solid-electrolyte (SE) separators is key for the commercialization of high-energy all-solid-state batteries (ASSBs). Herein, we report the preparation of Li _6 PS _5 Cl-based thin SE separators incorporating suitable binders for potential use in ASSBs by two scalable wet processing techniques: tape-casting with nitrile-butadiene rubber (NBR) and calendering with carboxylated nitrile butadiene rubber (XNBR). By means of tensile testing and electrochemical impedance spectroscopy, the influence of processing on the mechanical as well as the electrochemical properties of the resulting thin SE separators is investigated. A trade-off between the mechanical and electrochemical properties is observed, which is due to the inextricably linked microstructures (particle size, binder content and distribution, and porosity) induced by the two different processes. Thin SE separators prepared using the tape-casting method with the more well-distributed binder network demonstrate superior tensile mechanical properties compared to the ones prepared by the calendering method. The results provide insights into the processing-structure-property relationships of the thin SE separators, which will contribute to advancing the application of practical thin solid electrolytes in ASSBs.